Tropical Climate Conditions, Heat Stress, and the Effectiveness of Futsal Training Programs in Physical Education: A Systematic Literature Review - Uswatun Hasanah (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Tropical climate conditions characterized by high temperatures and humidity levels may increase heat stress during physical activity, potentially affecting the effectiveness of futsal training programs in physical education. Heat stress can impair physiological responses, physical performance, cognitive function, and learning outcomes among students participating in futsal activities. Objective: This study aimed to systematically analyze the relationship between tropical climate conditions, heat stress, and the effectiveness of futsal training programs in physical education settings. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, PubMed, ScienceDirect, Google Scholar, SINTA, and Garuda databases for publications from 2015–2025. Of the 312 articles initially identified, 25 studies met the inclusion criteria and were analyzed through thematic synthesis. Results: The review revealed that tropical environmental conditions (28–38°C; 65–92% relative humidity) significantly increased physiological strain, reflected by elevated core body temperature (38.5–39.8°C), heart rate (165–190 bpm), sweat loss (1.5–2.8 L/hour), and perceived exertion. Heat stress negatively affected futsal performance, resulting in reductions in VO?max (5–12%), repeated sprint ability (4–15%), agility (3–9%), technical accuracy (4–13%), and decision-making ability (6–14%). Furthermore, heat acclimatization, structured hydration, cooling strategies, and environmental monitoring were consistently associated with improved training effectiveness and reduced thermal strain. Conclusion: Tropical climate conditions substantially influence futsal training effectiveness through heat stress mechanisms. Integrating heat management strategies into physical education programs is essential to enhance student safety, optimize physiological adaptation, and improve learning outcomes in tropical environments.